2012
DOI: 10.1177/0022343311426167
|View full text |Cite
|
Sign up to set email alerts
|

Climate-related natural disasters, economic growth, and armed civil conflict

Abstract: Global warming is expected to make the climate warmer, wetter, and wilder. It is predicted that such climate change will increase the severity and frequency of climate-related disasters like flash floods, surges, cyclones and severe storms. This article uses econometric methods to study the consequences of climate-induced natural disasters on economic growth, and how these disasters are linked to the onset of armed civil conflict either directly or via their impact on economic growth. The results show that cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(103 citation statements)
references
References 35 publications
(65 reference statements)
1
98
0
Order By: Relevance
“…Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43). Other literature that assessed the influence of climate signals on armed-conflict outbreak risk did not report a robust connection (9,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Although a sequence of studies has suggested that a large number of outbreaks of armed conflicts in modern as well as premodern times have been associated with climatic variability (33,36,37,(39)(40)(41), the robustness of these findings and underlying mechanisms are controversially discussed (10,37,42,43). Other literature that assessed the influence of climate signals on armed-conflict outbreak risk did not report a robust connection (9,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The logistical constraints of terrorist attacks may differ substantially from those of many other types of violence studied here, possibly explaining why the structure of this response is inverted. Bergholt and Lujala (2012) are the only study to model the effect that floods and wind storms have on the onset of civil conflict , finding a small, negative and statistically insignificant effect. It is possible that these disasters, which are phenomenologically different from the rainfall and temperature variations studied above, have a fundamentally different impact on social conflict.…”
Section: Modern Global Datamentioning
confidence: 99%
“…Environmental shocks such as droughts, earthquake, cyclones and extreme flood are among the deadliest and disastrous natural disaster types that increased mortality 5 risks and economic losses affecting millions of populations (Gu, Gerland, Pelletier, & Cohen, 2015;Guha-Sapir, Below, & Hoyois, 2016). As exacerbated by climate change phenomenon, natural disasters are expected to affect millions of people across the world and impede current efforts in attaining long-term sustainable development goals (Intergovernmental Panel on Climate Change, 2012; Bergholt & Lujala, 2012;Hallegate, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies that have explored the adverse consequences of natural disasters on countries and concerned 10 population, particularly the poorest and marginalized groups (Wisner, Blaike, Cannon, & Davis, 2003;Kahn, 2005;Lin, 2010;Bergholt & Lujala, 2012;Bizzarri, 2012;Bradshaw, 2014;Kousky, 2016). However, there are currently few genderoriented research works that highlight the direct and disproportionate consequences of catastrophic events on women's life expectancy in relation to the socioeconomic and political conditions present in a country (Neumayer & Plumper, 2007).…”
Section: Introductionmentioning
confidence: 99%